(untitled) (Academia Journal of Medicine, 2024)
This study evaluated postoperative pain in pediatric patients after root canal treatment with two file systems: Manual K-files and Pedoflex Rotary files. Sixty children, aged 6-10, were randomized into two groups of 30. Pain was assessed using a Visual Analog Scale (VAS) at 6, 12, 24, and 48 hours post-treatment. Results showed significantly lower pain levels in the Pedoflex Rotary file group at all time points (mean VAS at 6 hours: 2.4 vs. 3.8; at 12 hours: 1.8 vs. 3.2; at 24 hours: 1.2 vs. 2.5; at 48 hours: 0.6 vs. 1.8). Pedoflex Rotary files provide a more comfortable postoperative experience.